2020
DOI: 10.14715/cmb/2020.66.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the expression levels of TNF-α, IL-6, hsCRP and sICAM-1 inflammatory factors, bone mineral density and nutritional status between diabetic and normal pregnant women

Abstract: To compare the ultrasound bone mineral density, nutritional status and inflammatory state of pregnant women with gestational diabetes mellitus (GDM) and those with normal blood glucose. Retrospective analysis of pregnant women who were prenatally examined and delivered in The 5th People's Hospital of Ji'nan from May 2015 to July 2017 was performed, including 68 subjects with normal blood glucose in the control group and 74 subjects with GDM in the experiment group. The bone mineral density, nutritional status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…17 In our study, the BMD of the GDM group was lower than that of the healthy population, but there was no statistical difference in calcium content between the two groups, which does not exclude statistical error and is also related to the small sample size included in this study. Wang Q et al 18 found in their study that the BMD of pregnant women with GDM was significantly lower than that of pregnant women with normal blood glucose, and believed that prevention of GDM in pregnant women was crucial for their bone health, which was similar to the results of this study. We found that there was a negative correlation between serum 25-hydroxyVitamin-D, PTH and BMD in the GDM group which was similar to the research results of Kramer et al 19 This may be attributed to the metabolic environment in pregnant women, in order to meet the growth and development of the fetus, regulating the increase of parathyroid hormone secretion, increasing the number of osteoclasts, promoting the dissolution of bone salts, bone calcium into the blood to supply nutrients needed for fetal growth, leading to the reduction of bone mineral density.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 87%
“…17 In our study, the BMD of the GDM group was lower than that of the healthy population, but there was no statistical difference in calcium content between the two groups, which does not exclude statistical error and is also related to the small sample size included in this study. Wang Q et al 18 found in their study that the BMD of pregnant women with GDM was significantly lower than that of pregnant women with normal blood glucose, and believed that prevention of GDM in pregnant women was crucial for their bone health, which was similar to the results of this study. We found that there was a negative correlation between serum 25-hydroxyVitamin-D, PTH and BMD in the GDM group which was similar to the research results of Kramer et al 19 This may be attributed to the metabolic environment in pregnant women, in order to meet the growth and development of the fetus, regulating the increase of parathyroid hormone secretion, increasing the number of osteoclasts, promoting the dissolution of bone salts, bone calcium into the blood to supply nutrients needed for fetal growth, leading to the reduction of bone mineral density.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 87%
“…The expression of cytokines, as well as the resulting immune response, may also be the result of cytokine gene polymorphism. Thus, cytokine gene polymorphisms can potentially contribute to the risk of recurrent miscarriage, especially gene polymorphisms associated with pro-inflammatory cytokines such as TNF-α, Il-1, Il-6, and IFNG [ 11 , 12 , 13 , 14 , 15 ]. TNF-α may directly promote tissue damage in pregnancy, as suggested by in vitro studies where TNF-α activated maternal monocytes bound to LFA-1 on placental syncytiotrophoblasts and induced apoptosis [ 16 ].…”
Section: The Role Of Tnf-α In Pregnancymentioning
confidence: 99%
“…Also, the average age and gestational age in this study are smaller than in the study Persico et al (28) . There are several reports related to the effect on the mood and mood of pregnant women, which needs more research (29)(30)(31)(32)(33)(34)(35) .…”
Section: Discussionmentioning
confidence: 99%